Immigration and Business Dynamics: Evidence from U.S. Firms - Parag Mahajan (Center for Economic Studies and ifo Institute (CESifo), 2022)
Prior literature on the economic impact of immigration has largely ignored changes to the composition of labor demand. In contrast, this paper uses a comprehensive collection of survey and administrative data to show that heterogeneous establishment entry and exit drive immigrant-induced job creation and a rightward shift of the productivity distribution in U.S. local industries. High-productivity establishments are more likely to enter and less likely to exit in high immigration environments, whereas low-productivity establishments are more likely to exit. These dynamics result in productivity growth. A general equilibrium model proposes a mechanism that ties immigrant workers to high-productivity firms and shows how accounting for changes to the employer distribution can yield substantially larger estimates of immigrant-generated economic surplus than canonical models of labor demand.
Keywords: J23; J61; L11; F22; 330; immigration; business dynamics; productivity; firm heterogeneity